A high-strength and high-temperature resistant lithium battery diaphragm material and preparation method thereof
By forming zirconium phosphate, silica and magnesium hydroxide composites in the lithium battery separator material, and organic modification and copolymer combination, the problem of poor compatibility of halogen-free flame retardant and polyvinylidene fluoride is solved, and the problem of poor compatibility of halogen-free flame retardant and polyvinylidene fluoride is improved. The flame retardant properties and mechanical properties of the material are ensured, ensuring stability and safety in high temperature environments.
Patent Information
- Application Number
- CN202411554153.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-11-04
AI Technical Summary
The existing halogen-free flame retardant has poor compatibility with polyvinylidene fluoride in lithium battery separators, resulting in improved flame retardant performance but decreased mechanical properties, especially in high temperature environments, and the stability and safety of the material are difficult to guarantee.
By forming a composite of zirconium phosphate, silica and magnesium hydroxide, and organically modified with silane coupling agent and GA and cinnamaldehyde, combined with SMG copolymer, the dispersion and phase of the inorganic flame retardant in the system are enhanced. Capacitance, improve the mechanical properties and flame retardant properties of battery separators.
It significantly improves the flame retardant performance and mechanical properties of lithium battery separator materials, enhances its thermal stability and safety in high temperature environments, and ensures the mechanical strength and flame retardant performance of the battery separator.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery diaphragm materials and relates to a high-strength and high-temperature resistant lithium battery diaphragm material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are composed of key components such as positive electrodes, negative electrodes, electrolytes, and separators. Among them, the battery separator plays a vital role. It ensures that the positive and negative electrodes of the battery are effectively isolated, avoiding short circuits caused by direct contact between the two electrodes. In addition, the separator provides a channel for ion transmission during the battery charging and discharging process, and its performance is directly related to the battery's energy storage capacity, cycle stability, and safety. The more excellent the comprehensive performance of the battery separator, the more significantly it can improve the overall performance and application potential of the battery. Generally, battery separators are expected to have the following performance characteristics: first, they have the ability to withstand electrolyte corrosion and high mechanical strength; second, they exhibit good wettability to the electrolyte; and finally, they have high safety performance and good flame retardant properties.
[0003] With the widespread application of battery separator materials, the use of halogen-free flame retardants is becoming more and more frequent. Among the many halogen-free flame retardants, nano flame retardants have received widespread attention due to their unique structure and nano-size effect. For example, graphene, zirconium phosphate, silicon dioxide, boron nitride, carbon nanotubes, etc. However, the compatibility between inorganic nanofillers and polyvinylidene fluoride is poor. Although the flame retardant properties have been improved, the mechanical properties of the composite material have been significantly reduced.
[0004] Zirconium phosphate is a two-dimensional nanosheet flame retardant material with excellent thermal stability and acid and alkali resistance. However, at a low addition amount, the flame retardant effect of zirconium phosphate on polyvinylidene fluoride is limited. If a large amount of inorganic zirconium phosphate is added, the mechanical strength of the polyvinylidene fluoride composite material will be reduced. The reason is that the compatibility between inorganic zirconium phosphate and the organic molecular chain of polyvinylidene fluoride is poor, causing the added zirconium phosphate nanoparticles to agglomerate in the polyvinylidene fluoride matrix, resulting in stress concentration. Therefore, the inorganic zirconium phosphate must be organically modified to enhance its interfacial compatibility with the polyvinylidene fluoride matrix. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength and high-temperature resistant lithium battery diaphragm material and a preparation method thereof. The present invention forms a composite by silicon dioxide and magnesium hydroxide, and organically modifies it by a silane coupling agent, and organically modifies zirconium phosphate by GA and cinnamaldehyde, and combines the introduction of SMG copolymer to further increase the dispersibility and compatibility of the inorganic flame retardant in the system, thereby strengthening the mechanical properties of the battery diaphragm material and improving its flame retardant properties.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A high-strength and high-temperature-resistant lithium battery diaphragm material comprises the following components by weight: 28-32 parts of polyvinylidene fluoride, 8-9 parts of functional filler, 2-3 parts of polyacrylamide, 0.5-0.8 parts of carboxymethyl cellulose and 70-80 parts of solvent.
[0008] As a preferred technical solution of the present invention, the solvent is N,N-dimethylformamide.
[0009] As a preferred technical solution of the present invention, the preparation method of the functional filler comprises the following steps:
[0010] Step 1: After mixing zirconium phosphate, anhydrous ethanol and cinnamaldehyde, GA is added and heated and stirred, cooled to room temperature, and the solid is filtered and vacuum dried to obtain modified zirconium phosphate;
[0011] Step 2: After mixing silica and deionized water, add magnesium chloride hexahydrate and perform ultrasonic treatment, slowly dropwise add sodium hydroxide aqueous solution and stir, let stand and filter, wash the solid, and dry to obtain composite particles;
[0012] Step 3: placing the composite particles in anhydrous ethanol and stirring and dispersing them, adding a silane coupling agent, heating and stirring, filtering and washing the solids, and drying them to obtain prefabricated particles;
[0013] Step 4: After the modified zirconium phosphate, SMG copolymer, composite particles and initiator are melt-extruded, granulated to obtain a functional filler.
[0014] As a preferred technical solution of the present invention, there are numerous Bronsted acid sites and Lewis acid sites between the layers of zirconium phosphate, which enables it to catalyze carbonization during the combustion process, helps to promote the carbonization reaction of polyvinylidene fluoride, and thus improves the flame retardant properties of polyvinylidene fluoride battery separator materials.
[0015] Furthermore, zirconium phosphate, as a layered nanomaterial, can play a barrier role in the thermal degradation process, and can form a physical barrier in the battery separator material in combination with silicon dioxide and magnesium hydroxide, which can play a role in heat insulation and heat absorption. Through the combined action of the three, it can effectively block the transfer of heat, thereby improving the temperature resistance of the battery separator material. Reduce the generation of heat and combustible gases. At the same time, zirconium phosphate can also enhance the strength of the carbonized layer, making it less prone to damage, thereby shortening the time for the formation of a stable carbonized layer, and promoting the formation of a carbon layer, playing a role in heat insulation and oxygen isolation and slowing down the escape of combustible gases.
[0016] As a preferred technical solution of the present invention, in step one, the stirring and mixing is stirring at a temperature of 35-40°C for 20-30 minutes; the heating stirring is stirring at a temperature of 70-76°C for 8-10 hours; the vacuum drying is placing in an oven at a temperature of 80-90°C and vacuum drying to constant weight; the mass ratio of the zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.0-3.4:35-40:1.5-1.8:0.5-0.6; the GA is 3,5-diamino-1,2,4-triazole; the GA added by the present invention has a high nitrogen content and a stable heterocyclic structure, and is widely used as a flame retardant. After the zirconium phosphate is organically modified, the Schiff base structure and the benzene ring structure are introduced to improve the thermal stability and flame retardant properties of the battery separator material.
[0017] As a preferred technical solution of the present invention, in step 2, the ultrasonic treatment is ultrasonic treatment at a frequency of 200-300W for 5-8min; the stirring is stirring at a speed of 350-400r / min for 3-4h; the standing time is 24h; the washing is washing with deionized water until the filtrate is neutral; and the drying is drying at a temperature of 70-80°C to constant weight.
[0018] As a preferred technical solution of the present invention, in step 2, the mass ratio of the silicon dioxide, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 1.8-2.1:10-12:0.5-0.6:12-13; the mass fraction of the sodium hydroxide aqueous solution is 15%; and the silicon dioxide is mesoporous silicon dioxide with a pore size of 10-20 nm.
[0019] As a preferred technical solution of the present invention, in step three, the heating and stirring is stirring at a temperature of 50-60°C for 5-6h; the washing is washing 3 times with anhydrous ethanol; and the drying is drying at a temperature of 80°C to constant weight.
[0020] As a preferred technical solution of the present invention, in step three, the mass ratio of the composite particles, anhydrous ethanol and silane coupling agent is 1.0-1.3:5.5-5.5:0.5-0.6; the silane coupling agent is vinyl triethoxysilane.
[0021] As a preferred technical solution of the present invention, in step 4, the melt extrusion parameters are 180-210°C melt temperature, 80-150r / min main screw speed, and 20-45r / min feeding screw speed;
[0022] As a preferred technical solution of the present invention, in step 4, the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and initiator is 4.0-5.0:12-14:8.0-8.2:0.40-0.43; the initiator is diisopropylbenzene peroxide.
[0023] As a preferred technical solution of the present invention, the SMG copolymer is a styrene-methyl methacrylate-glycidyl methacrylate terpolymer, which is used as a high thermal stability compatibilizer, wherein the styrene monomer content is 15wt%, the methyl methacrylate monomer content is 80wt%, and the glycidyl methacrylate monomer content is 5wt%; the SMG copolymer as a high thermal stability compatibilizer can enhance the interaction between the inorganic flame retardant and the system material, ensure the uniform distribution of the inorganic flame retardant in the matrix, and form a continuous barrier network. This network structure can not only improve the mechanical strength of the composite material, but also effectively maintain the dimensional stability and structural integrity of the material under high temperature environment. Not only the thermal stability and flame retardancy of the battery separator material are improved, but also the compatibility of the components of the battery separator material is significantly improved.
[0024] The invention discloses a method for preparing a high-strength and high-temperature resistant lithium battery separator material. The method comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and a solvent at 70-80°C for 20-30 minutes, adding carboxymethyl cellulose and a functional filler and stirring at 1000-1200 r / min for 45-60 minutes to obtain the separator.
[0025] Beneficial effects of the present invention:
[0026] The present invention forms a composite by silicon dioxide and magnesium hydroxide, and performs organic modification by a silane coupling agent, and organically modifies zirconium phosphate by GA and cinnamaldehyde, and combines the introduction of SMG copolymer to further increase the dispersibility and compatibility of the inorganic flame retardant in the system, thereby enhancing the mechanical properties of the battery separator material and improving its flame retardant properties. DETAILED DESCRIPTION
[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments. Example 1
[0028] A high-strength and high-temperature resistant lithium battery diaphragm material comprises the following components by weight: 28 parts of polyvinylidene fluoride, 8 parts of functional filler, 2 parts of polyacrylamide, 0.5 parts of carboxymethyl cellulose and 70 parts of N,N-dimethylformamide.
[0029] The preparation method of the functional filler comprises the following steps:
[0030] Step 1: After stirring zirconium phosphate, anhydrous ethanol and cinnamaldehyde at 35°C for 20 minutes, 3,5-diamino-1,2,4-triazole was added and stirred at 70°C for 8 hours, cooled to room temperature, filtered to obtain solids, washed with anhydrous ethanol for 3 times, and vacuum dried at 80°C to constant weight to obtain modified zirconium phosphate; wherein the mass ratio of zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.0:35:1.5:0.5;
[0031] Step 2: After mixing silica and deionized water, add magnesium chloride hexahydrate, ultrasonicate at a frequency of 200W for 5 minutes, slowly add sodium hydroxide aqueous solution, stir at a speed of 350r / min for 3 hours, filter after standing for 24 hours, take the solid, wash with deionized water until the filtrate is neutral, dry to constant weight at 70°C to obtain composite particles; wherein the mass ratio of silica, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 1.8:10:0.5:12; the mass fraction of the sodium hydroxide aqueous solution is 15%; the silica is mesoporous silica with a pore size of 10nm;
[0032] Step 3: After the composite particles are placed in anhydrous ethanol and stirred and dispersed, vinyl triethoxysilane is added and stirred at 50°C for 5 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 80°C to constant weight to obtain prefabricated particles; wherein the mass ratio of the composite particles, anhydrous ethanol and vinyl triethoxysilane is 1.0:5.5:0.5;
[0033] Step 4: melt-extrude the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide, and then granulate to obtain a functional filler; wherein the melt extrusion parameters are a melt temperature of 180°C, a main screw speed of 80r / min, and a feeding screw speed of 20r / min; and the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide is 4.0:12:8.0:0.40.
[0034] The preparation method of the high-strength and high-temperature resistant lithium battery separator material comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and a solvent at 70° C. for 20 minutes, adding carboxymethyl cellulose and a functional filler and stirring at 1000 r / min for 45 minutes to obtain the separator. Example 2
[0035] A high-strength and high-temperature resistant lithium battery diaphragm material comprises the following components by weight: 29 parts of polyvinylidene fluoride, 8.3 parts of functional filler, 2.3 parts of polyacrylamide, 0.6 parts of carboxymethyl cellulose and 73 parts of N,N-dimethylformamide.
[0036] The preparation method of the functional filler comprises the following steps:
[0037] Step 1: After stirring zirconium phosphate, anhydrous ethanol and cinnamaldehyde at 37°C for 25 minutes, 3,5-diamino-1,2,4-triazole was added and stirred at 72°C for 8.5 hours, cooled to room temperature, filtered to obtain solids, washed with anhydrous ethanol for 3 times, and vacuum dried at 83°C to constant weight to obtain modified zirconium phosphate; wherein the mass ratio of zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.1:37:1.6:0.53;
[0038] Step 2: After mixing silica and deionized water, add magnesium chloride hexahydrate, ultrasonicate at a frequency of 230W for 6 minutes, slowly add sodium hydroxide aqueous solution, stir at a speed of 360r / min for 3.5 hours, filter after standing for 24 hours, take the solid, wash with deionized water until the filtrate is neutral, dry to constant weight at 75°C to obtain composite particles; wherein the mass ratio of silica, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 1.9:10.8:0.55:12.5; the mass fraction of the sodium hydroxide aqueous solution is 15%; the silica is mesoporous silica with a pore size of 15nm;
[0039] Step 3: After the composite particles are placed in anhydrous ethanol and stirred and dispersed, vinyl triethoxysilane is added and stirred at 55°C for 5.5 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 80°C to constant weight to obtain prefabricated particles; wherein the mass ratio of the composite particles, anhydrous ethanol and vinyl triethoxysilane is 1.1:5.5:0.53;
[0040] Step 4: melt-extrude the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide, and then granulate to obtain a functional filler; wherein the melt extrusion parameters are a melt temperature of 190°C, a main screw speed of 105r / min, and a feeding screw speed of 28r / min; and the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide is 4.3:12.5:8.1:0.41.
[0041] The preparation method of the high-strength and high-temperature resistant lithium battery separator material comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and a solvent at 75° C. for 25 minutes, adding carboxymethyl cellulose and a functional filler and stirring at 1060 r / min for 50 minutes to obtain the separator. Example 3
[0042] A high-strength and high-temperature resistant lithium battery diaphragm material comprises the following components by weight: 31 parts of polyvinylidene fluoride, 8.6 parts of functional filler, 2.8 parts of polyacrylamide, 0.7 parts of carboxymethyl cellulose and 78 parts of N,N-dimethylformamide.
[0043] The preparation method of the functional filler comprises the following steps:
[0044] Step 1: After stirring zirconium phosphate, anhydrous ethanol and cinnamaldehyde at 38°C for 27 minutes, 3,5-diamino-1,2,4-triazole was added and stirred at 74°C for 9.5 hours, cooled to room temperature, filtered to obtain solids, washed with anhydrous ethanol for 3 times, and vacuum dried at 87°C to constant weight to obtain modified zirconium phosphate; wherein the mass ratio of zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.3:38:1.7:0.55;
[0045] Step 2: After mixing silica and deionized water, add magnesium chloride hexahydrate, ultrasonicate at a frequency of 260W for 7 minutes, slowly add sodium hydroxide aqueous solution, stir at a speed of 380r / min for 3.5 hours, filter after standing for 24 hours, take the solid, wash with deionized water until the filtrate is neutral, dry to constant weight at 75°C to obtain composite particles; wherein the mass ratio of silica, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 2:11.5:0.55:12.5; the mass fraction of the sodium hydroxide aqueous solution is 15%; the silica is mesoporous silica with a pore size of 15nm;
[0046] Step 3: After the composite particles are placed in anhydrous ethanol and stirred and dispersed, vinyl triethoxysilane is added and stirred at 55°C for 5.5 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 80°C to constant weight to obtain prefabricated particles; wherein the mass ratio of the composite particles, anhydrous ethanol and vinyl triethoxysilane is 1.2:5.5:0.57;
[0047] Step 4: melt-extrude the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide, and then granulate to obtain a functional filler; wherein the melt extrusion parameters are a melt temperature of 200°C, a main screw speed of 120r / min, and a feeding screw speed of 35r / min; and the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide is 4.7:13.5:8.1:0.42.
[0048] The preparation method of the high-strength and high-temperature resistant lithium battery separator material comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and a solvent at 75° C. for 25 minutes, adding carboxymethyl cellulose and a functional filler and stirring at 1130 r / min for 55 minutes to obtain the separator. Example 4
[0049] A high-strength and high-temperature resistant lithium battery diaphragm material comprises the following components by weight: 32 parts of polyvinylidene fluoride, 9 parts of functional filler, 3 parts of polyacrylamide, 0.8 parts of carboxymethyl cellulose and 80 parts of N,N-dimethylformamide.
[0050] The preparation method of the functional filler comprises the following steps:
[0051] Step 1: After stirring zirconium phosphate, anhydrous ethanol and cinnamaldehyde at 40°C for 30 minutes, 3,5-diamino-1,2,4-triazole was added and stirred at 76°C for 10 hours, cooled to room temperature, filtered to obtain solids, washed with anhydrous ethanol for 3 times, and vacuum dried at 90°C to constant weight to obtain modified zirconium phosphate; wherein the mass ratio of zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.4:40:1.8:0.6;
[0052] Step 2: After mixing silica and deionized water, add magnesium chloride hexahydrate, ultrasonicate at a frequency of 300W for 8 minutes, slowly add sodium hydroxide aqueous solution, stir at a speed of 400r / min for 4 hours, filter after standing for 24 hours, take the solid, wash with deionized water until the filtrate is neutral, dry to constant weight at 80°C to obtain composite particles; wherein the mass ratio of the silica, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 2.1:12:0.6:13; the mass fraction of the sodium hydroxide aqueous solution is 15%; the silica is mesoporous silica with a pore size of 20nm;
[0053] Step 3: After the composite particles are placed in anhydrous ethanol and stirred and dispersed, vinyl triethoxysilane is added and stirred at 60°C for 6 hours, the solid is filtered out, washed with anhydrous ethanol for 3 times, and dried at 80°C to constant weight to obtain prefabricated particles; wherein the mass ratio of the composite particles, anhydrous ethanol and vinyl triethoxysilane is 1.3:5.5:0.6;
[0054] Step 4: melt-extrude the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide, and then granulate to obtain a functional filler; wherein the melt extrusion parameters are a melt temperature of 210°C, a main screw speed of 150r / min, and a feeding screw speed of 45r / min; and the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and dicumyl peroxide is 5.0:14:8.2:0.43.
[0055] The preparation method of the high-strength and high-temperature resistant lithium battery separator material comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and a solvent at 80° C. for 30 minutes, adding carboxymethyl cellulose and a functional filler and stirring at 1200 r / min for 60 minutes to obtain the separator.
[0056] Comparative Example 1
[0057] Compared with Example 3, the difference in Comparative Example 1 is that vanillin is used instead of cinnamaldehyde, and the other components, preparation steps and parameters are the same.
[0058] Comparative Example 2
[0059] Compared with Example 3, Comparative Example 2 is different in that cinnamaldehyde is not used, and the remaining components, preparation steps and parameters are the same.
[0060] Comparative Example 3
[0061] Compared with Example 3, Comparative Example 3 is different in that magnesium chloride hexahydrate is not used, and the remaining components, preparation steps and parameters are the same.
[0062] Comparative Example 4
[0063] Compared with Example 3, Comparative Example 4 is different in that vinyltriethoxysilane is not used, and the other components, preparation steps and parameters are the same.
[0064] Comparative Example 5
[0065] Compared with Example 3, Comparative Example 5 is different in that no SMG copolymer is used, and the other components, preparation steps and parameters are the same.
[0066] Comparative Example 6
[0067] Compared with Example 3, Comparative Example 6 is different in that step 1;
[0068] Step 1: After stirring anhydrous ethanol and cinnamaldehyde at 38°C for 27 minutes, 3,5-diamino-1,2,4-triazole was added and stirred at 74°C for 9.5 hours, cooled to room temperature, zirconium phosphate was added and stirred, anhydrous ethanol was removed, and the mixture was washed with anhydrous ethanol for 3 times, and vacuum dried at 87°C to constant weight to obtain a mixture; the mixture was used instead of modified zirconium phosphate;
[0069] The remaining components, preparation steps and parameters were the same.
[0070] After the diaphragm materials prepared in Examples 1-4 and Comparative Examples 1-6 were cured into diaphragms, the following tests were performed respectively. The test results are shown in Table 1.
[0071] Flame retardant performance: Test the limiting oxygen index according to GB / T2406.
[0072] Mechanical properties: The membrane was cut into a dumbbell shape with a length of 6 mm and a width of 4 mm, and stretched at 30°C and a stretching rate of 5 mm / min to test the tensile strength.
[0073] Table 1
[0074]
[0075] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the tensile strength and flame retardant properties of the battery separator materials obtained in Examples 1-4 of the present invention are significantly better than those in Comparative Examples 1-6. This is because the present invention introduces a benzene ring structure with rigidity and thermal stability by chemically connecting the interlayer of zirconium phosphate through an imine bond between GA and the aldehyde group. Due to the high nitrogen content and stable heterocyclic structure of GA, the flame retardant properties and thermal stability of zirconium phosphate are improved. By forming a magnesium hydroxide precipitate on the surface of silicon dioxide, the self-agglomeration phenomenon can be effectively reduced. Then, the prefabricated particles obtained by modification with a silane coupling agent participate in a copolymerization reaction with the modified zirconium phosphate through a carbon-carbon double bond, so that it forms a chemical bond connection with the SMG copolymer, improves the dispersion state in the polyvinylidene fluoride system, improves the flame retardant properties of the battery separator material, and can also play a dual role of strengthening and toughening.
[0076] In addition, the epoxy groups in the SMG copolymer molecular chain are opened and the hanging hydroxyl groups can be connected with the hydroxyl groups on the surface of inorganic materials through hydrogen bonds, and the methyl methacrylate phase in the SMG copolymer has good compatibility with polyvinylidene fluoride. The compatibility of modified zirconium phosphate and prefabricated particles in the polyvinylidene fluoride system is further increased through the methyl methacrylate phase and the styrene phase, thereby enhancing the mechanical properties of the battery separator material and improving its flame retardant properties.
[0077] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A high-strength and high-temperature resistant lithium battery diaphragm material, characterized in that: The components include the following by weight: 28-32 parts of polyvinylidene fluoride, 8-9 parts of functional filler, 2-3 parts of polyacrylamide, 0.5-0.8 parts of carboxymethyl cellulose and 70-80 parts of solvent; Wherein, the preparation method of the functional filler comprises the following steps: Step 1: After mixing zirconium phosphate, anhydrous ethanol and cinnamaldehyde, GA is added, heated and stirred, cooled to room temperature, and solids are filtered and vacuum dried to obtain modified zirconium phosphate; wherein the mass ratio of the zirconium phosphate, anhydrous ethanol, cinnamaldehyde and GA is 3.0-3.4:35-40:1.5-1.8:0.5-0.6; and the GA is 3,5-diamino-1,2,4-triazole; Step 2: After mixing silica and deionized water, adding magnesium chloride hexahydrate and ultrasonically treating, slowly dropping sodium hydroxide aqueous solution and stirring, filtering after standing, washing the solid, and drying to obtain composite particles; wherein the mass ratio of silica, deionized water, magnesium chloride hexahydrate and sodium hydroxide aqueous solution is 1.8-2.1:10-12:0.5-0.6:12-13; Step 3: placing the composite particles in anhydrous ethanol, stirring and dispersing them, adding a silane coupling agent, heating and stirring, filtering and washing the solids, and drying them to obtain prefabricated particles; wherein the mass ratio of the composite particles, anhydrous ethanol and the silane coupling agent is 1.0-1.3:5.5-5.5:0.5-0.6; and the silane coupling agent is vinyl triethoxysilane; Step 4: After melt-extrusion of the modified zirconium phosphate, SMG copolymer, composite particles and initiator, granulation is performed to obtain a functional filler; wherein the mass ratio of the modified zirconium phosphate, SMG copolymer, composite particles and initiator is 4.0-5.0:12-14:8.0-8.2:0.40-0.43; and the SMG copolymer is a styrene-methyl methacrylate-glycidyl methacrylate terpolymer.
2. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: The solvent is N,N-dimethylformamide.
3. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step one, the stirring and mixing is stirring at 35-40°C for 20-30 minutes; the heating stirring is stirring at 70-76°C for 8-10 hours; and the vacuum drying is placing in an oven at 80-90°C for vacuum drying to constant weight.
4. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step 2, the ultrasonic treatment is performed at a frequency of 200-300 W for 5-8 min; the stirring is performed at a speed of 350-400 r / min for 3-4 h; and the standing time is 24 h.
5. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step 2, the washing is performed by using deionized water until the filtrate is neutral; and the drying is performed at a temperature of 70-80° C. to a constant weight.
6. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step 2, the mass fraction of the sodium hydroxide aqueous solution is 15%.
7. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step three, the heating and stirring is stirring at 50-60° C. for 5-6 hours; the washing is washing 3 times with anhydrous ethanol; and the drying is drying at 80° C. to constant weight.
8. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step 4, the melt extrusion parameters are 180-210° C. melt temperature, 80-150 r / min main screw speed, and 20-45 r / min feeding screw speed.
9. The high-strength and high-temperature-resistant lithium battery separator material according to claim 1, characterized in that: In step 4, the initiator is dicumyl peroxide.
10. A method for preparing a high-strength and high-temperature resistant lithium battery separator material according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: mixing polyvinylidene fluoride, polyacrylamide and solvent at 70-80°C for 20-30 minutes, adding carboxymethyl cellulose and functional filler and stirring at 1000-1200 r / min for 45-60 minutes to obtain the product.
Citation Information
Patent Citations
Preparation method of flame-retardant organic / inorganic composite membrane
CN104103793A
Heat-resistant flame-retardant composite diaphragm for lithium ion battery
CN111370633A